2000
DOI: 10.1366/0003702001949564
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Emission Derived from Dipicolinic Acid, its Sodium, and its Calcium Salts

Abstract: Aqueous solutions of the calcium and sodium salts of dipicolinic acid (DPA) were shown to have weak fluorescence when excited at wavelengths near 300 nm, but no fluorescence was observed from DPA alone. Upon UV irradiation at 254 nm the fluorescence of all three forms increases dramatically. The emission spectrum of calcium-DPA (CaDPA) has a maximum at 406 nm with full width at half-maximum of 70 nm. Changes in the absorption spectrum of the irradiated solution and the fact that the changes neither in absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…Relatively fast methods have been developed to extract CaDPA chemically and then detect it or its acid form, dipicolinic acid, by mass spectrometry, 9,10 luminescence 11,12 or fluorescence. 13 Yet another method employs a quartz wire to collect the particles, as well as to pyrolize them using current induced heat, then gas chromatography to separate the volatilized components, and a time-of-flight ion mobility spectrometer to detect DPA. 14 Although these latter methods provide a relatively high degree of discrimination and sensitivity, they still require significant time due to sample handling and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively fast methods have been developed to extract CaDPA chemically and then detect it or its acid form, dipicolinic acid, by mass spectrometry, 9,10 luminescence 11,12 or fluorescence. 13 Yet another method employs a quartz wire to collect the particles, as well as to pyrolize them using current induced heat, then gas chromatography to separate the volatilized components, and a time-of-flight ion mobility spectrometer to detect DPA. 14 Although these latter methods provide a relatively high degree of discrimination and sensitivity, they still require significant time due to sample handling and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent method [22] using 100 mM Tris buffer at pH 7.6 provides adequate buffering for the acid extract, and a Ca 2+ concentration required to achieve essentially complete formation of CaDPA chelate. Other researchers have reported that the reproducibility and consistency of the fluorescence intensity were found to be highly pH dependent [18].…”
Section: Cadpamentioning
confidence: 88%
“…As shown in Fig 2 the exposed absorption spectrum of CaDPA shows only minor changes compared with the absorption spectrum of an unexposed CaDPA solution. Nudelman et al, [18] reported that low-dose treatment with 254 nm UV irradiation caused only slight changes in the absorption spectrum of CaDPA. However, irradiation of 10 uM solutions of CaDPA in HEPES buffer at higher intensity and for longer durations, resulted in absorption spectra that changed substantially.…”
Section: Cadpamentioning
confidence: 99%
“…Previous fluorescence excitation-emission studies by Nudelman et al and Bronk et al for DPA, CaDPA and DPA-ion in aqueous solution [18][19][20][21] indicated the minimal or no fluorescence for DPA prior to UV irradiation but substantial fluorescence after irradiation at 255 nm. The present study is motivated by the fact that more detailed excitation-emission studies are needed to understand the fluorescence of endospores.…”
Section: Introductionmentioning
confidence: 93%